Optimization of Computer Communication Monitoring System for Wind Turbine Speed. (21st December 2021) - Li, Zuoshan
Abstract : This article first studies the operating principles of wind turbines, focusing on the analysis of the structure and working principles of permanent magnet direct-drive wind turbines. According to the actual needs of the wind power system, the monitoring objects of the monitoring system are determined, and the overall monitoring plan for wind power generation is proposed to realize real-time analysis of the operating characteristics of the wind power system. At the same time, it pointed out the great significance of the wind power generation simulation experiment system and focused on the wind speed modeling. In terms of hardware research and analysis, relevant sensors, high-speed data acquisition cards, etc., were selected, and relevant signal conditioning circuits were designed, and a permanent magnet direct-drive wind power generation system simulation monitoring platform was constructed. In terms of software, LabVIEW was chosen as the design language of the monitoring system, and it pointed out the advantages of using LabVIEW in this monitoring system. Finally, the system uses the laboratory permanent magnet direct-drive wind turbine as the monitoring object. The practicality and accuracy of the system are verified through experiments such as permanent magnet motor power test, motor speed test, database system test, and remote monitoring test. The experimental results show that the monitoring system has a friendly interface and perfect functions and has important practicability and reference in the field of wind power monitoring.